Prevalence and determinants of under and overnutrition among under five children in Bengo Province, Angola - Brito, Miguel (2017)
Introduction - Children malnutrition is a major public health problem in developing countries. Identifying the risk factors of malnutrition and determining their magnitude is necessary to develop nutritional interventions to confront this problem. Aim - The aim of this study is to assess the determinants associated to under and overnutrition in children under 5 years in Bengo Province, Angola. Methods - A community-based cross-sectional study was used during August to September 2014. A questionnaire adapted from ProPAN 14, willing to collect data on children’s general health care, breastfeeding and feeding practices, food ingestion in the previous 24 hours, socioeconomic characteristics and water supply, was applied. Anthropometric measures were collected from all children and mothers to determine their nutritional status Univariate and multivariate analysis were performed to identify factors related to malnutrition. Results - The survey was conducted during 30 days and comprehended 808 children aged 0 to 59 months, from which 50.5% were male Infant wasting, stunting, and underweight prevalence were 7.7%, 35.8%, and 15.2% respectively. The prevalence of overnutrition was 4.2%, with 3.4% of overweight and 0.8% obese. Risk factors significantly associated with stunting were increased age of children (OR = 4.45, 95%CI 1.98, 9.95), low birth weight (OR = 2.23; 95%CI 1.20, 4.11), insufficient information about child feeding among caregivers (OR = 2.23; 95%CI 1.20, 4.15), and non-exclusive breastfeeding (OR = 1.88; 95%CI 1.30, 2.76). Inadequate dietary diversity was significantly associated with a higher risk of wasting (OR = 2.97; 95%CI 1.21, 7.32). Both stunting and wasting were significantly associated with diarrhea in the previous two weeks (OR = 1.50; 95%CI 1.07, 2.08 and OR = 3.08; 95%CI 1.48, 6.41, respectively) and living in a household with more than two children aged under five (OR = 1.50; 95%CI 1.04, 2.18 and OR = 3.19; 95%CI 1.51, 6.77, respectively). Conclusion - Undernutrition is common among children under 5 years in Bengo province. Age, birth weight, child feeding knowledge, type of breastfeeding, dietary diversity, diarrhea morbidity and the number of under-five children living at household were related to undernutrition. The presented results evidence the need of nutritional interventions in order to control children malnutrition risk factors.